2017
DOI: 10.1017/jfm.2017.549
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of a self-similar adverse pressure gradient turbulent boundary layer at the verge of separation

Abstract: The statistical properties are presented for the direct numerical simulation (DNS) of a self-similar adverse pressure gradient (APG) turbulent boundary layer (TBL) at the verge of separation. The APG TBL has a momentum thickness based Reynolds number range from Re δ2 = 570 to 13800, with a self-similar region from Re δ2 = 10000 to 12300. Within this domain the average non-dimensional pressure gradient parameter β = 39, where for a unit density β = δ 1 P ′ e /τ w , with δ 1 the displacement thickness, τ w the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 47 publications
11
105
1
Order By: Relevance
“…Mellor and Gibson (1966) defined the pressure velocity u p = δ * /ρdP e /dx, which is related to the Clauser pressure-gradient parameter as β 2 = u p /u τ . Similarly, it is possible to define an outer-scaled APG parameter as u p /U e , as in the study by Kitsios et al (2017), who also considered a strongly-decelerated APG with β = 39. The ratio u p /U e is shown in Figure 7 for the four wing cases under consideration.…”
Section: Boundary-layer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mellor and Gibson (1966) defined the pressure velocity u p = δ * /ρdP e /dx, which is related to the Clauser pressure-gradient parameter as β 2 = u p /u τ . Similarly, it is possible to define an outer-scaled APG parameter as u p /U e , as in the study by Kitsios et al (2017), who also considered a strongly-decelerated APG with β = 39. The ratio u p /U e is shown in Figure 7 for the four wing cases under consideration.…”
Section: Boundary-layer Developmentmentioning
confidence: 99%
“…The use of β to characterize the pressuregradient magnitude and to identify near-equilibrium TBLs was introduced by Clauser (1954Clauser ( , 1956, together with Mellor and Gibson (1966), who developed a theoretical framework for such TBLs. Although in the very strong APG conditions beyond x ss /c 0.95 the β parameter may not be adequate to characterize the effect of the pressure gradient on the TBL (as in the work by Kitsios et al (2017)), the APG on the flow upstream can be assessed in terms of β. The fact that the lower-Re wings are subjected to a larger u p /U e ratio is connected to their stronger wall-normal velocity, as discussed below.…”
Section: Boundary-layer Developmentmentioning
confidence: 99%
“…The latter case is the one considered in the present work for adverse-pressure-gradient turbulent boundary layers. This explains the lower values of the shape factor obtained by Clauser 3 and Lee 26 compared to the higher (close to separation) values of Stratford 27 , Mellor and Gibson 19 or Kitsios et al 28 for the same value of m. Besides, Schofield also found that near-equilibrium is not possible when m < −0.3 which is a threshold in accordance with the results of Head 23 and close to the value of −1/3 given by Townsend 20 . These two conclusions are also observable in the work of Clauser 3 .…”
Section: Please Cite This Article As Doi:101063/15125496mentioning
confidence: 76%
“…All turbulent terms (3.7)-(3.15) and the viscosity (3.16) are represented analogously to the analysis of George & Castillo (1993) as products of an x-dependent and an η-dependent quantity. In contrast to most previous incompressible analyses, where the displacement thickness δ * is anticipated as length scale L 0 (x) for the outer scaling (Townsend 1956b;Castillo et al 2004;Kitsios et al 2016Kitsios et al , 2017,…”
Section: Outer-layer Ansatz Functionsmentioning
confidence: 80%
“…Thus, the similarity analysis itself only provides templates for conditions that must be fulfilled by possible characteristic scales in case of self-similarity; consequently, without the specific choice of scales, the results are not applicable to real flow data. In analogy to the analysis of incompressible TBLs, such as by George & Castillo (1993), Castillo et al (2004), Maciel et al (2006) and Kitsios et al (2016Kitsios et al ( , 2017, see § 2.2.2, a separation-of-variables approach is used for the present analysis. Every quantity Ψ (x, y) of the compressible two-dimensional boundary-layer equations is hereby assumed to consist of a combination of ansatz functions; for example, Ψ (x, y) = Φ(x)φ(η), where Φ(x) and φ(η) depend only on either the streamwise position x or the wall-normal position η = y/L 0 (x).…”
Section: Methodsmentioning
confidence: 99%